Informal Status and Taking Charge: The Different Roles of OBSE, P-J Fit, and P-S Fit - Deng, Chuanjun; Liao, Shudi; Liu, Zhiqiang; Zhang, Yucheng; Bao, Yan (Frontiers in Psychology, 2020)
Status in an organization is considered a significant antecedent to an employee's work-related behaviors. However, the relationship between knowledge workers' informal status and "taking charge" has been ignored in previous human resource management (HRM) research. Based on the self-consistency theory, this study examines the mechanisms underlying the influence of knowledge workers’ informal status on taking charge. Data were collected from 337 dyads of employees and their immediate supervisors in 24 enterprises and companies. Based on moderated mediation analysis, results indicated that knowledge workers’ informal status is positively related to taking charge and organization-based self-esteem (OBSE). OBSE fully mediated the relationship between knowledge workers’ informal status and taking charge, while person-job fit (P-J fit) and person-supervisor fit (P-S fit) each moderated the relationship between knowledge workers’ informal status and OBSE, in addition to the indirect effect of knowledge workers’ informal status on taking charge. Specifically, the indirect effect was strongest when P-J fit or P-S fit was high. The theoretical and managerial implications of the findings, limitations of the study, and future research directions are discussed.